Inhibition of B-cell activating factor activity using active compounds from Physalis angulata in the mechanism of nephrotic syndrome improvement: A computational approach - Kardani, Astrid K.; Fitri, Loeki E.; Samsu , Nur; Subandiyah , Krisni; Endharti, Agustina T.; Nugrahenny, Dian; Wibowo, Syahputra (Narra Sains Indonesia, 2024)
Nephrotic syndrome, a multifaceted medical condition characterized by significant proteinuria, has recently prompted a reorientation of research efforts toward B-cell-mediated mechanisms. This shift underscores the pivotal role played by B-cells in its pathogenesis. The aim of this study was to explore potential therapeutic pathways, with specific attention given to compounds found in Physalis angulata, including withanolides, such as physalins, which constitute one of the five distinct withanolide subgroups identified in Physalis angulata. Furthermore, the study assessed the monoclonal antibody belimumab, designed to target B-cell activating factor (BAFF) and its associated receptors (TACI, BCMA, and BAFF-R). Various research techniques were employed, encompassing data mining, bioactivity analysis, Absorption, Distribution, Metabolism, Excretion, and Toxicity (ADMET) profiling, molecular modeling, and docking studies. Withanolide was demonstrated as a potential inhibitor for the protein BAFF, showing a binding energy of -7.1 kcal/mol. Physalin F emerged as the leading candidate inhibitor for the protein TACI, with a binding energy of -8.3 kcal/mol. Similarly, withanolide was identified as the top inhibitor candidate for the protein BCMA, exhibiting a binding energy of -7.0 kcal/mol. The most favorable interaction with BAFF-R was physalin F, which displayed a binding energy of -8.0 kcal/mol. Moreover, molecular dynamic simulation suggested that physalin F was able to maintain protein stability, hence being a good inhibitor candidate for BAFF-R and TACI proteins. The results of this investigation demonstrated substantial promise, indicating that these withanolides and withaphysalin A compounds derived from Physalis angulata offer alternative avenues for B-cell targeting. Consequently, this study presents opportunities for pioneering treatments in the management of nephrotic syndrome.